1996
DOI: 10.1590/s0037-86821996000500006
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response to Salmonella typhi lw human Schistosomiasis mansoni

Abstract: Antibody response toActivation of the immune system has been demonstrated during acute schistosomiasis2 3 27 and, although modulation of both the cellular15" and humoral1819 immune responses occur later during the chronic phase of the disease, high levels of anti-Schistosom a m an son i antibodies are still detectable. However, the ability of infected individuals to mount an immune response to unrelated antigens has not yet been clearly established.It has been shown that some Schistosom ain fected individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…However, we also have previously shown in human schistosomiasis an impaired capacity to produce specific antibodies to Salmonella 16 . Therefore, the association in schistosomiasis of a reduced functional reserve of macrophages with the impaired production of specific antibodies 16 20 24 and the deficient Tlymphocyte function 17 appear to be insufficient to overcome the Salmonella infection as seems to be the case of chronic salmonellosis associated with schistosomiasis.…”
Section: Figure 1 -Influence Of the Bacterial Load On The Phagocytosisupporting
confidence: 54%
“…However, we also have previously shown in human schistosomiasis an impaired capacity to produce specific antibodies to Salmonella 16 . Therefore, the association in schistosomiasis of a reduced functional reserve of macrophages with the impaired production of specific antibodies 16 20 24 and the deficient Tlymphocyte function 17 appear to be insufficient to overcome the Salmonella infection as seems to be the case of chronic salmonellosis associated with schistosomiasis.…”
Section: Figure 1 -Influence Of the Bacterial Load On The Phagocytosisupporting
confidence: 54%
“…There is substantial evidence of variability between populations in vaccine immunogenicity: notably, impaired responses to yellow fever vaccine were observed in Uganda, compared to Switzerland, in a study that found reduced vaccine virus replication and neutralising antibody production and persistence, in the context of elevated innate and adaptive immune response activation, among Ugandan volunteers [50]. There is evidence, for other vaccines, of differences (such as Th2 bias) in the response between people with and without schistosomiasis [7, 10], and of modulation of vaccine responses by other helminth species [8, 9]. Key factors in helminth-vaccine interactions are likely to include vaccine characteristics (live, replicating, protein or toxoid), prior exposure to environmental organisms or pathogens homologous to the vaccine, and the nature of the desired response (cellular or antibody).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the effects are less clear. Helminth infections can modulate vaccine-induced responses against tetanus [7], influenza [8], cholera [9], and Salmonella typhi [10]. T-helper (Th)1 responses are important for protective immunity against intracellular bacteria and viruses, while helminths characteristically induce Th2 [11] and immunoregulatory responses, both of which can down-regulate Th1 pathways [8].…”
Section: Introductionmentioning
confidence: 99%
“…En algunos de esos casos ocurre un cuadro peculiar en que la progresión de la enfermedad sigue un desarrollo favorable al huésped (3)(4)(5)(6). Así, la agresión al tejido del huésped como, por ejemplo, la fibrosis y la inflamación, podría ocurrir de forma menos grave, permitiendo una mayor supervivencia, como se observó en nuestro material.…”
Section: Sexo*unclassified